Pembelajaran Diferensiasi Dalam Perspektif Al-Qur’an: Telaah Qs. An-Nahl Ayat 125 Berdasarkan Tafsir Fi Zhilalil Qur’an - Fatwai Nasikhah; Enjang Burhanudin Yusuf (CV. ITTC INDONESIA, 2025)
This article aims to analyze the Islamic educational values embedded in the concept of da'wah bil hikmah wal mau'izhah al-hasanah as explained by Sayyid Qutb in Fi Zhilal al-Qur'an, with a specific focus on QS. An-Nahl:125 and its relevance to differentiated instruction. Using a qualitative-descriptive method with a textual approach, this study examines Qutb's exegetical writings as the primary data source, supported by classical and contemporary Islamic educational literature as secondary sources. The findings indicate that Qutb interprets the three core principles hikmah, mau'izhah al-hasanah, and mujadalah billati hiya ahsan as pedagogical foundations that systematically correspond to dimensions of differentiated instruction. Hikmah serves as the basis for content differentiation, emphasizing material adjustment based on students' readiness and context; mau'izhah al-hasanah represents process differentiation through empathetic communication and varied scaffolding strategies; while mujadalah inspires product differentiation that promotes critical dialogue and higher-order thinking skills. These values generate concrete educational indicators, including adaptive instruction, empathetic communication, moral exemplification, and civilized argumentative dialogue. The study reveals that Qutb's interpretation aligns with major Islamic scholars such as al-Ghazālī, Ibn Khaldūn, and al-Qaradāwī, reinforcing the conceptual-operational relevance of Qur'anic guidance for modern Islamic education. The implications suggest that Islamic educational practices can be strengthened through value-based instructional models that prioritize humanization, justice, empathy, and intellectual refinement, contributing to developing holistic learners capable of navigating contemporary challenges through Qur'anic ethics and pedagogical wisdom.